Adjunctive Coiling in Flow Diverter Treatment Does Not Prevent Delayed Rupture: A Nationwide Survey - Shigeru Miyachi; Reo Kawaguchi (Neurointervention)
Purpose Delayed rupture (DR) can occur even after successful deployment of flow diverters (FDs). Although coiling is often added to reduce the risk of rupture in high-risk intracranial aneurysms, its effectiveness remains unproven. To assess current practice in Japan, a questionnaire was distributed to evaluate the effect of coiling on rupture prevention. Materials and Methods A retrospective survey was sent to 124 institutions with qualified FD practitioners, receiving 76 responses (61%). A total of 5,527 patients treated with FDs were included in the study, and clinical records of 5,211 aneurysms were analyzed. Results DRs (excluding intraprocedural accidents) occurred in 36 cases (0.7%). Of 1,286 aneurysms treated with FD and coiling, 9 (0.7%) ruptured. Ruptured aneurysms in the FD with coiling group were located in the supraclinoid segment (4 cases), paraclinoid internal carotid artery (ICA) (3 cases), and basilar artery (2 cases), of which 7 were classified as giant (diameter >20 mm). In the FD-alone group, 55% (15/27) of ruptured aneurysms were located in the cavernous ICA. Time to rupture ranged from 1 to 2,220 days with no significant difference between groups, except for 1 exceptionally delayed case. Outcomes were worse in the FD with coiling group, where 67% (6/9) had a modified Rankin Scale score of 6. The DR rate was identical between the FD-alone and FD with coiling groups. Conclusion Coiling does not appear to prevent rupture after FD treatment. Aneurysms treated with coiling tended to be larger, to rupture earlier, and to have worse outcomes, probably due to selection bias. Routine loose coiling may provide psychological reassurance but lacks proven efficacy as a preventive measure.